18.0k views
0 votes
-4(2x + 3)= 2x + 6 - (8x +2)

1 Answer

1 vote

The given equation is expressed as

- 4(2x + 3) = 2x + 6 - (8x + 2)

The first step is to expand the brackets by multiplying the terms inside the bracket by the term outside. It becomes

(- 4 * 2x) + (- 4 * 3) = 2x + 6 - 8x - 2

- 8x - 12 = 2x + 6 - 8x - 2

The next step is to collect like terms. It becomes

- 8x + 8x - 2x = 6 - 2 + 12

- 2x = 16

Dividing both sides of the equation by - 2, it becomes

- 2x/- 2 = 16/-2

x = - 8

User Tomwyr
by
5.1k points